Characterization of the thymus in Lrp4 myasthenia gravis: four cases - Koneczny, Inga; Marx, Alexander (Autoimmunity reviews, 2019)
Myasthenia gravis (MG) is an autoimmune disease of the neuromuscular junction. Most patients have pathogenic autoantibodies against the acetylcholine receptor (AChR). In the last years a novel subpopulation of MG patients has been described that harbors antibodies against low-density lipoprotein receptor-related protein 4 (Lrp4), another postsynaptic neuromuscular antigen. In early-onset AChR MG (EOMG), the thymus plays an important role in immunopathogenesis, and early thymectomy is beneficial. It is still unknown if the thymus plays any role in Lrp4-MG. In this pilot study, we compared thymus samples from four patients with Lrp4-MG (one pre-treated with immunosuppressive drugs), four non-MG controls and five EOMG patients (not pretreated with immunosuppressive drugs).
Available online 08 November 2018
Gesehen am 15.01.2020